TODDLER WITH ENTEROBIASIS - Salman Alfarisi (Jurnal Agromedicine Unila: Jurnal Kesehatan dan Agromedicine, 2015)
Enterobiasis is a disease caused by Enterobius vermicularis. The disease is spread to all levels of society, in cities and villages in the high and low social, children and adults. However, compared to adults this disease has a high prevalence in children. Personal hygiene is a very important factor on the occurrence of Enterobiasis. Patient, 2 years and 10 months old female, came to the clinic brought by her parents because they found two worm in patient’s stool at night, the worm was small, fine as hair, cream-colored.The last few days the patient often feels restless and difficult to sleep at night. Physical examination found no abnormalities, but the long and dirty nails. Patients was diagnosed with enterobiasis and treated with pyrantel pamoate 125 mg single dose. Parents were educated to teach their children about personal hygiene with washing hand before eat and after defecation, cut the nails and keep the nail hygiene. In this case the role of parents is very important. [J Agromed Unila 2015; 2(1):39-42]Keywords: bad personal hygine, enterobiasis, pyrantel pamoat, toddler